Nghiên cứu chế tạo điện cực compozit CNTs/V2O5 bằng phương pháp điện hóa - Hồng Thắm, Nguyễn Thị; Tuấn Hùng, Lê Vũ; Quyết, Đỗ Hữu (Vietnam Journal of Chemistry, 2016)
For highly demand of high performance energy storage market, supercapacitors (also known as electrochemical capacitors or ultra-capacitors), have been studied intensively due to their properties of high power density, long cycle life. The major challenge for most commercial supercapacitors based on double-layer capacitance is the low energy density due to the limitation of electrode materials’ surface area. In this study, we developed a nanocomposite electrode having both double-layer and pseudo-capacitance. Vanadium pentoxide was electrochemically prepared onto a buckypaper with a three-dimensional structure on a nanometer scale, so it enhances the electron transfer, shortens the ion diffusion paths and leads to high electrochemical performance. From cyclic voltammetry discharging experiments in an electrolyte (LiCl 5 M), the composite showed a specific capacitance of 243 F/g, about three times higher than commercial double-layer capacitors, demonstrating the superior electrochemical performance and rendering it a promising candidate for supercapacitor application. Keywords. Cyclic voltammetry, supercapacitor, vanadium pentoxide